Meningkatkan Keterampilan Komunikasi Interpersonal Siswa Melalui Konseling Kelompok Dengan Teknik Penguatan Positif Pada Siswa Kelas VIII 1 SMP Swasta Nur Azizi - Fitriani Lubis (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine whether positive reinforcement technique group counseling services can improve the interpersonal communication skills of class VIII-1 students at Nur Azizi Private Middle School for the 2022/2023 academic year. This research uses research in counseling guidance (PTBK) which is carried out in 2 cycles, namely cycle I and cycle II. Each cycle consists of planning, action, observation and reflection. The subjects of this research were 5 students in class VIII-1 of Nur Azizi Private Middle School who had interpersonal communication skills scores in the low category obtained from the questionnaire that had been distributed. This research data was collected using an interpersonal communication skills questionnaire with 31 statement items which were valid and reliable with a score of 0.771. Data were analyzed descriptively by comparing the percentages achieved before and after group counseling. Based on the results of the research that has been carried out, it can be concluded that before being given positive reinforcement technique group counseling, the average level of students' interpersonal communication skills was 55.8 in the low category. After being given positive reinforcement technique group counseling in cycle I, the average score of students' interpersonal communication skills level increased to 70.2 in the medium category with a success achievement of 60% and in cycle II the average score of students' interpersonal communication skills level increased to 106. 2 in the high category with 100% success. So there was a significant increase in interpersonal communication skills after group counseling was carried out using positive reinforcement techniques for class VIII-1 students at Nur Azizi Private Middle School for the 2023/2024 academic year.